Transcranial Direct Current Stimulation of the Medial Prefrontal Cortex Has No Specific Effect on Self-referential Processes - Mainz, Verena; Britz, Sara; Forster, Saskia Doreen; Drüke, Barbara; Gauggel, Siegfried (Frontiers in Human Neuroscience, 2020)
The processing of self-referential information can be influenced by Transcranial Magnetic Stimulation. The present randomized controlled study investigated whether similar effects can be elicited through the application of transcranial Direct Current Stimulation (tDCS) regarding the “self-serving bias” (SSB) and the “mnemic neglect effect” (MNE). Seventy-five healthy males (Mage = 25; SD = 4.3) were investigated in a between group design with random assignment by applying anodal, cathodal, or sham tDCS to the medial prefrontal cortex (mPFC). After stimulation participants judged if 80 personality traits (40 positive, 40 negative) were self-descriptive or not. Finally, participants had to recall the previously presented adjectives. All three stimulation groups showed the expected SSB and MNE. Still, and contrary to our hypotheses, tDCS revealed neither an significant interaction effect between groups and valence concerning the number of chosen self-referential traits (F(2,72) = 1.36, p = .26, ƞ2G = .02) nor an interaction effect between groups, valence, and self-reference concerning the percentage of recalled words (F(2,71) = 0.69, p = .50, ƞ2G = .01). However, post-hoc inspection of effect sizes revealed that less negative traits were indicated as self-referential in the anodal compared to the cathodal group (ES: -.59; CI: -1.16 – -.03). Moreover, participants showed - regardless of self-reference and type of stimulation - a better recall with tDCS in comparison to sham stimulation. Our results indicate that tDCS of the mPFC in healthy young men has no influence on the SSB and MNE. However, tDCS seems to improve memory performance.